The co-construction of the ‘innovation space’: hybrid collectives, networks and innovation capacity - Oliveira, L.; Carvalho, H. (35th 4S Annual Meeting: STS in Global Contexts. Annual Meeting of the Society for Social Studies of Science (4S) with JSSTS (Japanese Society for Science and Technology Studies), 2008)
The R&D system in Portugal was reorganised using a model designed to improve links with firms in order to facilitate the transfer of knowledge and to improve innovation capacity. In this paper a survey is used as the basis for an analysis on if, why and to what extent firms and other entities linked with each other and how this affected their innovation capacity. Methods of Multiple Correspondence and Cluster analysis were applied. Our discussion of the results led us to question the notion of “transfer of knowledge” and the role of economic theory in the construction of this reality.